Determinants of sleep quality among older people - Nungki Marlian Yuliadarwati; Agus Hariyanto; Sujono Sujono (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Sleep quality is a key indicator of health in later life, yet it often deteriorates as individuals age, particularly among those living in institutional settings. In nursing homes, biological changes interact with daily routines and limited physical activity, potentially aggravating sleep disturbances. Understanding these interactions is essential for developing feasible interventions for elderly residents. Methods: This cross-sectional study was conducted among 288 older adults residing in nursing homes in Malang, Indonesia. Participants were selected using purposive sampling based on predefined criteria. Physical activity was assessed using the Global Physical Activity Questionnaire (GPAQ), sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and anxiety using the Depression Anxiety Stress Scale (DASS). Multivariate linear regression was applied to examine associations between demographic factors, anxiety, physical activity, and sleep quality. Results: The regression model explained 37.9% of the variance in PSQI scores (R2 = 0.379). While higher physical activity levels significantly predicted better sleep quality (β = -0.415, p < 0.001). advanced age (β = 0.043, p = 0.018) and female sex (β = 0.482, p = 0.003) were significantly linked to worse sleep outcomes. Neither anxiety (β = -0.069, p = 0.071) and employment history (β = -0.079, p = 0.086) were not significantly associated with sleep quality. Conclusion: Among the factors examined, physical activity demonstrated the strongest association with sleep quality in elderly nursing home residents. These findings highlight the potential value of activity-based programs as part of routine care, while also pointing to the need for sleep interventions that account for age-related and sex-specific differences.